INTEGRASI ETIKA PROFESI ISLAM DALAM PENGUATAN KAPABILITAS MANAJER PENDIDIKAN ABAD 21 - Hajjin Mabrur; Mizan Syahroni; Ali Nuruddin Nurul Ilmi (Eduvis : Jurnal Manajemen Pendidikan Islam, 2022)
The managerial landscape of the 21st century demands educational leaders who possess not only technical and cognitive competencies but also a deeply rooted ethical orientation capable of responding to the complexities of a rapidly changing world. Within the context of Islamic education, this ethical orientation finds its most profound expression in the concept of Islamic professional ethics, which encompasses the values of integrity, accountability, justice, and spirituality as the bedrock of professional conduct. This study aims to examine the integration of Islamic professional ethics as a foundational framework for strengthening the managerial capabilities of Islamic education managers in the 21st century. Employing a systematic library research methodology, this study analyzed and synthesized relevant academic literature from reputable sources published between 2017 and 2022. Data were analyzed using the Miles and Huberman interactive model. The findings propose a conceptual model called the IQLAS Framework (Integrity, Quality, Leadership, Accountability, Spirituality), which operationalizes five dimensions of Islamic professional ethics into concrete 21st-century managerial competencies. This model contributes to the academic field of Islamic educational management and offers practical guidance for developing ethical and competent educational leaders.